2018
DOI: 10.14336/ad.2017.1125
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in Older Adults with Cardiovascular Disease: Cause, Effect or Both?

Abstract: Cardiovascular disease (CVD) has been associated with an increased risk of frailty, but the direction of the association remains unclear. This study set out to examine the bidirectional longitudinal association between CVD and frailty over an extended period of time. Data are from 1432 older adults (aged 65-88yrs) of the Longitudinal Aging Study Amsterdam (LASA), who were followed for 17 years. At baseline and follow-up, CVD was assessed through self-report, medication use and medical records, and classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 33 publications
3
49
0
Order By: Relevance
“…[22,42] The Longitudinal Aging Study Amsterdam (LASA) revealed that community-dwelling elderly people with HF had an increased risk of frailty, independent of potential confounders such as sex, age and multimorbidity. [42] The Health ABC Study, which had a follow-up of 11.4 years and included 2,825 people with a mean age of 74 years at baseline, demonstrated that frailty is independently associated with risk of HF in older people. [22]…”
Section: Frailty Syndrome Epidemiologymentioning
confidence: 99%
“…[22,42] The Longitudinal Aging Study Amsterdam (LASA) revealed that community-dwelling elderly people with HF had an increased risk of frailty, independent of potential confounders such as sex, age and multimorbidity. [42] The Health ABC Study, which had a follow-up of 11.4 years and included 2,825 people with a mean age of 74 years at baseline, demonstrated that frailty is independently associated with risk of HF in older people. [22]…”
Section: Frailty Syndrome Epidemiologymentioning
confidence: 99%
“…In these algorithms, data from different sources are combined [21]. Algorithms were constructed for seven cardiovascular diseases (CVD) (angina pectoris, myocardial infarction, coronary artery disease, congestive heart failure, peripheral arterial disease, cardiac arrhythmia and cerebrovascular accident), diabetes mellitus and osteoarthritis [22][23][24]. Using these algorithms, respondents were categorized as definitely, possibly or not having a disease, contradictory data, or as missing when there are no data available.…”
Section: Chronic Disease and Composite Algorithmsmentioning
confidence: 99%
“…These outcomes are known and well-established. The relationship between acute coronary disease and frailty showcases a bidirectional configuration [12]. Frailty is reported to be more common in patients presenting with a cardiovascular disease-irrespective of whether frailty was an instigator of this incident or a mere result of it.…”
Section: Role Of Frailty In Alleviating Disease Burdenmentioning
confidence: 99%